Magnetic resonance imaging pattern in natalizumab-associated progressive multifocal leukoencephalopathy - Yousry, Tarek A.; Gass, Achim (Annals of neurology, 2012)
Objective: Natalizumab is an effective treatment for patients with multiple sclerosis (MS) that is associated with a risk of progressive multifocal leukoencephalopathy (PML). Recommendations were published in 2006 to improve early diagnosis of PML using magnetic resonance imaging (MRI). However, due to the small number of MS patients initially diagnosed with PML, the imaging criteria could only be derived from PML lesions in patients with human immunodeficiency virus. Therefore, there is an urgent need to assess the MRI characteristics of PML in MS patients to update the existing recommendations. Methods: In this retrospective review, the first 40 natalizumab-treated MS patients diagnosed with PML in the postmarketing setting were identified, of whom 22 (10 with clinically diagnosed immune reconstitution inflammatory syndrome) fulfilled the inclusion criteria for this study. Magnetic resonance images were analyzed according to predefined criteria by 5 independent readers. Results: The most frequent lesion pattern in early scans from PML patients was that of large (>3 cm, 15 of 18), subcortical (18 of 18), T2 or fluid-attenuated inversion recovery hyperintense (18 of 18), T1-hypointense (17 of 18), and diffusion-hyperintense (15 of 15) lesions, with a sharp border toward the gray matter and an ill-defined border toward the white matter (18 of 18) on T2-weighted images. We could detect contrast enhancement in 41% (7 of 17) of the cases on the first scan at clinical presentation. Interpretation: Attention to characteristic MRI patterns, especially the presence of contrast enhancement, and the subcortical location may have utility in screening and early diagnosis of PML in natalizumab-treated MS patients. ANN NEUROL 2012;72:779-787